313. Estimation of the radiation absorbed dose to the choroid plexuses in 68Ga-NODAGA-RGD PET. (December 2018) - Amato, E.; Cicone, F.; Auditore, L.; Baldari, S.; Prior, J.O.; Gnesin, S.
Abstract : Purpose: Aim of this work was to estimate the radiation absorbed dose to the choroid plexuses in 68 Ga-NODAGA-RGD PET, a tracer used to study angiogenic processes that is significantly taken-up by these vascular structures[1] . Methods: Five patients who underwent a clinical research protocol of PET-CT with 68 Ga-NODAGA-RGD and contrast-enhanced brain MRI were considered for our dosimetric estimations. We set up Monte Carlo simulations in GAMOS (GEANT4-based Architecture for Medicine-Oriented Simulations), which exploited the MRI images as input. In particular, a voxelized region containing choroid plexuses was defined according to the morphological data obtained from the segmentation of MRI images. The radioactive source was uniformly distributed inside the choroid plexuses. A second set of Monte Carlo simulations was carried out using a simplified geometry of choroid plexuses and the results were compared with the MRI-based simulations. A further comparison was made with doses evaluated through the OLINDA sphere model. Results: OLINDA sphere model systematically overestimates the dose of about +50% with respect to the MRI-based Monte Carlo simulation. On the other hand, simulations using the simplified geometry show a good agreement with the MRI-based ones. This result is significant, allowing to use short time-consuming calculations and within a simple geometrical environment. Conclusions: Because of their markedly elongated and curved morphology, human choroid plexuses are a typical example of tissue structures that cannot be accurately represented by a sphere, when radiation absorbed dose assessments are of concern. Given that the internal dosimetry of choroid plexuses is worth of particular attention when using radiopharmaceuticals that exhibit a selective uptake, Monte Carlo simulation can be regarded as the gold standard for the dosimetry of these structures.